A compression device versus compression stockings in long-term therapy of lower limb primary lymphoedema after liposuction. (2nd January 2020) - Karafa, Marian; Karafová, Anna; Szuba, Andrzej
Abstract : Objective: Primary lymphoedema is rare and in most cases develops in the lower extremities. In some cases, conservative treatment is insufficient and can be supported by surgical procedure. The aim of this case study was to show the difference in the effectiveness of a compression wrap device and compression stockings in the treatment of primary lymphoedema. Method: Before and after liposuction the patient was treated on an outpatient basis every day for three weeks. This consisted of complex decongestive therapy (CDT) including manual lymph drainage, tailored exercises, skin and nail care, compression therapy and intermittent pneumatic compression. After CDT, the patient was provided with a flat-knit compression garment. Measurements were taken at one week and at three months of wearing the compression garment. The oedema severity was measured by summary calculation method. For both healthy and swollen limbs, the sum of circumferences taken at nine fixed measuring points was determined. The difference between these sums expressed in percents was presented as a relative metric coefficient of leg lymphoedema (RMCL). Results: At the start of therapy, the difference in circumference between the healthy and swollen limb was 21.85%. After CDT (RMCL: 13.46%), the patient was provided with a flat-knit compression stocking (class 3). After one week, the RMCL was 15.92%, while after three months RCML was 20.84%. Because fluid retention was observed the patient was again treated with CDT (RMCL: 13.89%). The patient was provided with compression stocking (class 4). After one week of wearing, the RMCL was 15.77%, while after three months RMCL was 20.26%. As the results proved unsatisfactory, the patient was treated with CDT (RMCL: 13.60%) and a combination of two class 4 compression stockings was used. After one week, RMCL was 14.91%, while after three months RMCL was 19.25%. As the effects of oedema reduction were insufficient, the patient was treated again with CDT (RMCL: 13.89%) and advised to replace one of the stockings with a CirAid device (adjustable compression wrap). After one week, RMCL was 14.18% and after three months RMCL was 14.76%. The patient then qualified for liposuction (RMCL: 7.81%). At three months after surgery, the compression stocking was replaced by an adjustable compression wrap, to reduce the difference in circumference between healthy and swollen limbs (from 21.85 % to 8.68%). Conclusion: This case study shows that in primary oedema one class of compression garment is not always sufficient, nor is the combination of two garments with varying degrees of compression. In some cases, the situation requires the use of non-elastic leg binders such as a CircAid device which, thanks to its greater stiffness, helps improve clinical outcomes.